1987
DOI: 10.1159/000118638
|View full text |Cite
|
Sign up to set email alerts
|

Primary Projections of the Lateral Line Nerves in Adult Lampreys

Abstract: Primary lateralis projections in silver lampreys, Ichthyomyzon unicuspis, and young adult sea lampreys, Petromyzon marinus, were examined utilizing silver impregnation of degenerating fibers and transganglionic transport of horseradish peroxidase. Anterior lateral line nerve afferents terminate throughout the neuropil of the electroreceptive dorsal nucleus and in the lateral neuropil of the mechanoreceptive medial nucleus. The superficial ophthalmic, buccal and recurrent rami of the anterior lateral line nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…In particular, retrogradely labeled neurons were found mainly in a periventricular layer at the level of the respiratory motor column. This location could correspond at least in part to that of neurons of the dorsal and medial octavolateral nuclei described in previous studies (Nieuwenhuys, 1972;Northcutt, 1979;Bodznick and Northcutt, 1981;Ronan and Northcutt, 1987;Koyama et al, 1990;Koyama, 2005). As in the respiratory motor regions, retrogradely labeled neurons were both ipsi-and contralateral to the pTRG.…”
Section: Ascending Excitatory Projections From the Ola To The Ptrgsupporting
confidence: 85%
See 1 more Smart Citation
“…In particular, retrogradely labeled neurons were found mainly in a periventricular layer at the level of the respiratory motor column. This location could correspond at least in part to that of neurons of the dorsal and medial octavolateral nuclei described in previous studies (Nieuwenhuys, 1972;Northcutt, 1979;Bodznick and Northcutt, 1981;Ronan and Northcutt, 1987;Koyama et al, 1990;Koyama, 2005). As in the respiratory motor regions, retrogradely labeled neurons were both ipsi-and contralateral to the pTRG.…”
Section: Ascending Excitatory Projections From the Ola To The Ptrgsupporting
confidence: 85%
“…The OLA consists of three primary octavolateralis nuclei arranged dorsoventrally which receive multiple sensory inputs. More specifically, it has been described that the dorsal nucleus receives electroreceptive inputs, the medial nucleus receives mechanoreceptive inputs and the ventral nucleus receives vestibular inputs (Rovainen, 1979;Northcutt, 1979;Bodznick and Northcutt, 1981;Ronan and Northcutt, 1987;Koyama et al, 1990Nieuwenhuys, 1972. Interestingly, it has been reported that afferent projections of the glossopharyngeal and vagal nerves terminate in the OLA, especially in its medial and ventral nuclei (Koyama, 2005).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…8B,D). This confirms the findings of other investigators (Fritzsch et al 1984;Koyama et al 1990;Ronan and Northcutt, 1987;Ronan, 1988;Ronan and Bodznick, 1991). To investigate whether there are contralaterally projecting neurones in this area, HRP was injected into different sites of the contralateral rhombencephalic reticular formation (N=24) to fill commissural neurones retrogradely through their axons (eight injections in the ARRN, eight injections in the MRRN and eight injections in the PRRN; the typical sites of injection are shown in Fig.…”
Section: Contralaterally Projecting Neurones In the Medialsupporting
confidence: 92%
“…8C,E,F). Almost no crossing cells were found in the lateral part of the MON, which receives lateral line input from the head region (Ronan and Northcutt, 1987). Rostrocaudally, the commissural cells were located between the entrance of the PLLN and the root of the vagal nerve, but not in the rostral part of the MON (Fig.…”
Section: Contralaterally Projecting Neurones In the Medialmentioning
confidence: 97%
See 1 more Smart Citation